Children's Character Education in The Principles of Self-Identity Malay Perspective Tenas Effendy - Mukhtar, Zulfadhly; Selvi, Issaura Dwi; AH, Nurkamelia Mukhtar (JOYCED: Journal of Early Childhood Education, 2023)
The greatest challenge in the current era of globalization and modernization is to uphold and impart moral values and character to children. There are numerous cases where children lose their direction and ethics due to the influence of various media, technology, and foreign cultures. This research aims to examine the values of early childhood character education from the perspective of Malay identity principles by Tenas Effendy. The study employs a literature review method (library research). Data collection techniques involve studying literature and documentation of Tenas Effendy's writings on Malay Identity Principles. The data analysis technique used is content analysis. The research findings indicate that the values of children's character education in the Malay identity principles perspective of Tenas Effendy encompass eight aspects: religious character, honesty, hardworking nature, independence, responsibility, social concern, environmental awareness, and friendly/communicative nature. Therefore, implementing these noble values in children can help shape a strong foundation of character. This doesn't only prepare children for academic success but also builds a moral and ethical groundwork that will guide them in facing future challenges.